(untitled) (Gaceta Técnica, 2024)
The objective of this research was to evaluate the physical and mechanical properties of bricks using waste sludge from drinking water treatment plants and wastewater treatment plants. For this purpose, an experimental and comparative study was carried out where 20 bricks made with 50% waste sludge were selected as a sample, they were compared with 20 traditional bricks (Pyramid 18H). According to the results, it has been identified that the compressive strength in traditional bricks corresponds to 14,73 MPa; being within type IV and type V; meanwhile, the resistance in bricks with mud (Toby) is 7,11 MPa, the same as those considered in type I and II bricks